MORPHOLOGICAL VARIATION OF WHITEHEADâS RAT Maxomys whiteheadi (Thomas, 1894) (RODENTIA: MURIDAE) FROM KALIMANTAN AND SUMATRA - Sinaga, M. H.; Gorog, A J; Chinen, A (Masyarakat Zoologi Indonesia, 2007)
We conducted a study of morphological variation in Whiteheadâs rat (Maxomys whiteheadi) based on specimensÂ available at the Museum Zoologicum Bogoriense. A total of 224 adult specimens from the Indonesian islandâs of Sumatra and Kalimantan were examined using measurements of 17 skull and four external characters. Multiple analyses of variance demonstrated that 20 of characters measured varied significantly with location. Only breadth of zygomatic plate did not show a significant effect by location. One character, hind foot length, was significantly affected by sex, and the characters head and body length, breadth of braincase, and breadth of molar 1 showed a significant interaction (p< 0,05) between sex and location. Three distinct morphological groups of M. whiteheadi were recognized within Kalimantan using discriminant function analysis. These were: a West and East Kalimantan group; a Central Kalimantan group; and a North East Kalimantan group. No distinct morphological groups were observed among the Sumatra specimens. The discriminant analysis indicated that most of the variation (79,9%) distinguished the Kalimantan and Sumatra populations from one another.